Enhancing low frequency sound absorption of micro-perforated panel absorbers by using mechanical impedance plates. (February 2015) - Zhao, Xiaodan; Fan, Xiangqian
Highlights: Mechanical resonance absorption mechanism is introduced into traditional MPP. Multi-layer mechanical impedance plates can be adopted in the structure. The calculation of the proposed structure's acoustic absorptivity is finished. Sound absorptivity of MPP in low frequency is obviously improved. Abstract: Micro-perforated panel (MPP) absorbers have been widely used for noise control because of their environmental friendliness and attractive appearance. The fundamental absorbing mechanism of a conventional MPP absorber is cavity resonance absorption. Micro-perforated panel absorbers backed with mechanical impedance plates (MIP) are proposed to enhance the performance of low-frequency sound absorption, where conventional MPP absorbers cannot provide sufficient absorption in the case that the backed cavity is limited. Low-frequency sound waves penetrate the micro-perforated panel and are incident on the impedance plates, which will be effectively stimulated to vibrate when the frequency of the incident sound wave is close to resonance frequency of the plate. Due to the viscous material at the boundary, the mechanical impedance provides viscous damping, thereby enabling improved sound attenuation. The acoustic impedance of the proposed sound absorber is investigated using the transfer matrix method. The results of theoretical calculation are in good agreement with the experimental results. The composite structure combines the sound absorption mechanisms of cavity resonance and mechanical resonance. Low-frequency absorption is effectively enhanced without the need to increase the total thickness of the structure.